The Role of the Chloroplast in the Replication of Positive-Sense Single-Stranded Plant RNA Viruses - Budziszewska, Marta; Obrępalska-Stęplowska, Aleksandra (Frontiers in Plant Science, 2018)
Abstract Positive-sense single-stranded [ss(+)] plant RNA viruses are obligate intracellular parasites that infect many agriculturally important plants, leading to severe losses of crops. All known plant RNA viruses are characterized by small genomes encoding a limited number of multifunctional viral proteins. Viral pathogens are considered to be absolutely dependent on host. To facilitate genomic RNA replication, viruses must recruit numerous host proteins and other factors. The replication process depends on the virus – plant protein-protein, RNA -protein as well protein - lipid interactions. The recently published data provided strong evidence on important role of chloroplasts in viral RNA synthesis. Chloroplast is considered to be a multifunctional organelle, responsible for photosynthesis, as well generation of plant defense signaling molecules. The access to high throughput technologies based on proteomics, genomics, electron microscopy including especially three-dimensional tomography revealed that several groups of plant RNA viruses exploit chloroplasts double membranes to assemble viral replication complex (VRC). Some of chloroplast-related proteins were also reported to interact with viral proteins as well its genomic RNAs and participate in trafficking them to the chloroplast membranes, where the replication takes place. Most recently, the impact on viral RNA synthesis was also attributed to plant protein components of oxygen evolving complex, that may regulate virus replication. In this work we present the current knowledge on the important role of chloroplast in viral replication process.